Phân lập và xác định cấu trúc của các hợp chất tritecpen từ cây xạ đen - Sung và cộng sự, Trần Văn (Vietnam Journal of Chemistry, 2014)
Chemical investigation of Celastrus hindsii Benth. growing in Quang Binh province, Vietnam led to the isolation and structural elucidation of clionasterol, D:A-friedo-oleanane-3,21-dione, lup-20(29)-ene-3b-ol and lup-12-ene-3b-ol. Their structures were determined on the basis of MS, NMR spectra and comparison with reported data.